(untitled) (Nepal Journal of Epidemiology, 2024)
Background: Urinary incontinence (UI) is a common medical problem that seriously affects patients’ physical, psychological, social, and financial well-being. To identify the most effective drug management techniques, this retrospective study aimed to describe the demographics, etiology, and medical traits of people with UI. Methods: This retrospective study was conducted at Rumailah Hospital, Ambulatory Care Centre, and Hamad General Hospital to investigate UI risk factors, causes, and management practices in people aged ≥ 65 years within the Hamad Medical Corporation (HMC) in Qatar. Results: The 272 patients enrolled in the study had a marked male preponderance, and a larger percentage of non-Qatari residents than Qataris residents. Solifenacin (24.9%), Tolterodine (4.1%), and Oxybutynin (1.1%) were the most commonly administered anticholinergic drugs, while Tamsulosin (82.9%), Alfuzosin (14.5%), and Doxazosin (1.7%) were the most frequently prescribed alpha-blockers. Conclusion: This study underscores the importance of investigating UI in institutionalized older adult populations considering the limited research available in Qatar. The identified preventable risk factors can be proactively addressed to mitigate UI. This study also highlights the need for thorough documentation of the diagnosis and reasons for improving the standards of patient care. The findings of this study provide important information that can be used to design medication management methods for enhancing patient outcomes.